Mixed matrix membrane performance enhancement using alkanolamine solution - Nasir, R. (Elsevier, 2015)
Mixed matrix membranes (MMMs) containing diethanolamine (DEA) and carbon molecular sieve (CMS) in polyethersulfone (PES) were synthesized and characterized to study the efficiency of CO2 separation from CH4. The membranes were fabricated by adding fixed amount of CMS and polymer into a solvent with DEA at different concentrations. These membranes were characterized for physicochemical properties by employing field emission scanning electron microscopy (FESEM), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR). The permeability and selectivity studies were carried out by using pure carbon dioxide and methane in a small laboratory test cell. The characterization results revealed that the structure of the membranes was dense and non-porous. It was also found that carbon molecular sieve was uniformly distributed in the polymer matrix. The addition of DEA significantly enhanced the performance of the investigated MMMs such that the CO2 permeance and CO2/CH4 selectivity were enhanced up to 172.41 and 283.21 respectively at a pressure of 6bar. A comparison with the performance of a few other membranes decisively establishes the superiority of the membranes prepared and tested in this study. Â© 2015 Elsevier B.V.